Microbial load in indoor sport environments: new quality issues by molecular biology (Italian Journal of Public Health, 2004)
The quality of hygiene found in sporting environments represents an emergent requirement in societies of industrialised countries.Besides safety issues, the microbial load of indoor air, water and surfaces affects comfort and performance. Recent studies have identified fungi as the quantitatively most important component, of unhealthy indoor air.Few studies have been carried out regarding indoor sport, recreational and rehabilitative facilities, such as swimming pools, saunas and spas. The aim of our study is to determine the extent of fungal and microbial contamination in indoor swimming pool environments, by means of both morphological and molecular typing of isolated species.Establishment of appropriate standardised monitoring procedures prevents infections and improves quality.